Comparison of X-Ray and Morphological Changes in Pulmonary Sarcoidosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study consists in the study of radiological and morphological changes in sarcoidosis of the respiratory organs. The study involved 60 patients aged 25 to 65 years. The analysis of radiological manifestations of sarcoidosis was evaluated by the main indicators (symmetry of the lesion, size of the intra-thoracic lymph nodes, the presence of dissemination, pneumofibrosis). An extensive morphological study of biopsy samples with the study of quantitative and qualitative composition was carried out. . Changes in lung parenchyma and enlargement of mediastinal lymph nodes were detected in all patients of stage I-III. The components of the cellular elements of the inflammatory infiltrate did not differ at different stages of sarcoidosis.